Achmad Rifai MENINGKATKAN HASIL BELAJAR MENGGIRING BOLA PADA PERMAINAN SEPAK BOLA DENGAN MENGGUNAKAN PENDEKATAN BERMAIN - Rifai, Achmad (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2017)
ABSTRACT This research aims to improve learning outcomes dribbling on the game of football by using the approach play. The subjects were all students of class V SDN Kertawaluya III amounted to 24 people. Research methods using action research methods to design Kemmis and Taggart. The results obtained in the pre-cycle is an average value of 64.58 students with students who have not completed as much as 62.5%, whereas that have been completed as much as 37.5%. In the first cycle the average value of students increased to 68.75 with students who have not completed as much as 25%, while that has been completed as much as 75%. And the second cycle of the average value of students increased to 74.17 with students who have not completed as much as 12.5%, while that has been completed as much as 87.5%. Based on these results it can be concluded that by using the approach of learning outcomes dribble play in the game of football is increasing. That way physical education teachers can use the approach to play in the teaching process. Key words: Learning outcomes, Dribbling ball, Playing approach